Russian Orthodoxy under the Old Regime - Nichols, Robert L. (Robert Lewis), 1942- (Book collections on Project MUSE., 1974)
In this book, which is especially suitable for course use, eleven scholars examine one of the most important institutions of imperial Russia, the Orthodox church in the two centuries before the Russian revolution. The material is arranged in two sections, the first devoted to Orthodoxy's role in Russian social and cultural life and the second dealing with the church's relationship to the tsarist regime.